Transformasi Pembelajaran Pendidikan Kedokteran Akibat COVID-19 Sekarang dan Mendatang - Ryan Herardi; Niniek Hardini; Riezky Valentina Asteri; Lingga Etantyo Praditya; Shahnaz Medina (Jurnal Kedokteran Syiah Kuala, 2023)
Abstract. The rise of Coronavirus Disease 19 (COVID-19) pandemic in the late 2019 has affected every aspect of our lives, including the education and learning method. The medical education is also required to shift from face-to-face learning methods to distance-learning methods while maintaining its quality of learning. There are few learning methods applied in the medical education, such as lectures, small group discussions, laboratory activities, clinical skills activities and clinical rotations which involved doctor-patient interactions. All of these learning methods may eventually be transformed to adjust to the regulations of COVID-19 prevention which promote social distancing and prohibit gatherings.